Uses of the ‘sustainability’ formula in the health area: the example of volunteering practice in hospitals - Piccardi, Tatiana (The ESPecialist, 2014)
The term ‘sustainability’ and its variations has become what Krieg-Planque (2011, 2010) calls ‘formula’. In this paper, I propose to (i) discuss the use of the ‘sustainability’ formula in the health welfare from the experience of volunteers working in this area, reflecting on the causes and consequences of its diffusion; and (ii) investigate the usefulness of this linguistic-discursive concept for understanding the social contexts in which certain lexical items are circulating as a formula.